WISISI: TRANSFORMASI TARI-MUSIK PAPUA DARI RITUAL ADAT KE HIBURAN GLOBAL DIGITAL - Muhammad Ilham Mustain Murda (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
Wisisi, a dance-music form originating from the Dani community in the Papuan Highlands, was traditionally embedded in ritual practices as a medium of social cohesion, entertainment, and collective healing. Over the last decade, Wisisi has undergone a profound shift from ritual performance into popular entertainment, later evolving into digital music production performed on national and international stages. This article aims to examine the transformation of Wisisi from its ritual roots to its position as a global cultural expression. The study applies a qualitative approach, combining literature review, audiovisual documentation, and mini-ethnographic analysis of sources such as traditional performance archives, contemporary recordings, and the documentary Wisisi Nit Meke that won recognition at the Indonesian Film Festival in 2023. The findings reveal three major aspects of transformation: first, the transition of function from ritual practice to public celebration; second, the adaptation of Wisisi into electronic forms by younger musicians using digital production tools; and third, the dissemination of Wisisi across online platforms and international festivals. These changes demonstrate how Wisisi negotiates cultural identity in the digital era while raising concerns regarding commodification and the sustainability of indigenous values.